PELACAKAN FRAGMEN GEN PENYANDI ENZIM ß-KETOASIL-ACP SINTASE II (KAS II) DARI MESOKARP KELAPA SAWIT (ELAEIS GUINEENSIS JACQ. L.) - Yohanes Chandrawijaya; Teuku Tajuddin; Hermin Pancasakti Kusumaningrum; Anto Budiharjo (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2013)
The standard of quality is one of the determining values of crude palm oil as an international trade commodity. Better standard of quality for crude palm oil is a constant demand of the market. Quality improvement can be made by increasing the contents of oleic acid in the mesocarp of E. guinensis. Among the uses of oleic acid are as follows: anti-carcinogenic agent, anti-oxidant, source of pro-vitamin A, and source of Vitamin E. Oleic acid is a form of non-saturated fatty acid encoded by KAS II genes. The expression profiling of KAS II is achieved through isolation of total RNA by Trizol reagent, RNA purification, using DNAse RNAse free, synthesis of cDNA using Reverse Transcriptation PCR approach, and amplification of KAS II genes with Nested PCR approach. The amplification process of KAS II genes is carried out using both internal and external primers. The first step of the external primer PCR is F-KAS-1 and R-KAS-1. Internal primer of PCR in the second step is F-KAS-2 and R-KAS-2. The results of this research are fragments of KAS II genes between 1500–2000 bp. These amplicons are suitable with primers designed at the approximation of 1796 bp. Selection of three amplicons at the annealing temperatures of 54oC, 55.9oC, and 58oC shows good DNA band visualizations. Annealing at 58oC shows the best result with high intensity DNA band and no smear. Further research is needed to determine the accuracy of the amplicons through sequencing step. Keywords: KAS II, Elaeis guineensis, annealing, Nested PCR, RT-PCR